CHOICE OF TREATMENT FOR CROHN’S DISEASE OF THE COLON - Murad M. Mirzakhmedov; Mukhamedjan A. Akhmedov; F.D. Ortiqboyev (Central Asian Journal of Medicine, 2023)
Scientific novelty. The main modern diagnostic and surgical methods for the treatment of Crohn’s disease of the colon are highlighted. It has been established that in Crohn’s disease of the colon, the operation of choice is total colectomy, anterior resection of the rectum with the formation of an ileorectal anastomosis using circular staplers. At the same time, the frequency of postoperative complications decreases to 12.7%. The study included 84 patients who underwent conservative and surgical treatment in the proctological department of the 1st Republican Clinical Hospital of the Ministry of Health of the Republic of Uzbekistan. for the period from 2010 to 2022 for Crohn’s disease of the colon. Of these, 53 (63%) were men, 31 (37%) were women. The age of the patients ranged from 15 to 61 years. The average age was 37.1+1.2 years. Results. Indications for surgery for Crohn’s disease of the colon are a total lesion of the inflammatory-ulcerative process, the presence of intestinal and extra-intestinal complications, the ineffectiveness of conservative therapy and the progression of the disease.